Pertautan Islam dan Budaya Lokal dalam Ritual Rokat Tase’ (Studi di Perkampungan Nelayan Legung Batang-Batang Sumenep) - Misnatun Misnatun; Moh. Zainol Kamal (Tafhim Al-'Ilmi, 2021)
Abstrak Islamic thougt and culture go hand in hand without losing their respective identities and characteristics. Islamic thougt are carried out solemnly without losing their essence, as well as traditional rituals which are celebrated with joy and not lose their values and meaning. As for one form of linking these two elements, one of which is reflected in the 'rokat tase' ritual. The rokat tase' ritual is a ritual that is carried out on a regular basic-temporal as a form of gratitude for the sustenance given by God as well as a request to be kept away from calamity and distress Kata kunci: Islam, Budaya Lokal, Ritual, Rokat Tase’